Crystallographic texture formation in Fe-9wt%Si alloy during deformation and phase transition at high pressure. Issue 2 (10th March 2023) - Vasin, Roman N; Kunz, Martin; Wenk, Hans-Rudolf; Zepeda-Alarcon, Eloisa
SUMMARY: The seismic anisotropy of the Earth's solid inner core has been the topic of much research. It could be explained by the crystallographic preferred orientation (CPO) developing during convection. The likely phase is hexagonal close-packed iron (hcp), alloyed with nickel and some lighter elements. Here we use high energy synchrotron X-rays to study CPO in Fe-9wt%Si, uniaxially compressed in a diamond anvil cell in radial geometry. The experiments reveal that strong preferred orientation forms in the low-pressure body-centred cubic (bcc) phase that appears to be softer than pure iron. CPO is attributed to dominant 110<111> slip. The onset of the bcc→hcp transition occurs at a pressure of ≈15 GPa, and the alloy remains in a two phase bcc + hcp state up to 40 GPa. The hcp phase forms first with a distinct 112 0 maximum perpendicular to compression. Modelling shows that this is a transformation texture, which can be described by Burgers orientation relationship with variant selection. Experimental results suggest that bcc grains oriented with <100> parallel to compression transform into hcp first. The CPO of the hcp changes only slowly during further pressure and deviatoric stress increase at ambient temperature. After heating to 1600 K, a change in the hcp CPO is observed with alignment of (0001) planes perpendicular to compression that can be interpreted as dominant (0001)<112 0> slip, combined with 101 2<1 011> mechanical twinning, which is similar to the deformation modes suggested previously for pure hcp iron at inner core conditions.